2022
DOI: 10.3390/polym14050936
|View full text |Cite
|
Sign up to set email alerts
|

pH-Responsive Nanocarriers in Cancer Therapy

Abstract: A number of promising nano-sized particles (nanoparticles) have been developed to conquer the limitations of conventional chemotherapy. One of the most promising methods is stimuli-responsive nanoparticles because they enable the safe delivery of the drugs while controlling their release at the tumor sites. Different intrinsic and extrinsic stimuli can be used to trigger drug release such as temperature, redox, ultrasound, magnetic field, and pH. The intracellular pH of solid tumors is maintained below the ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(46 citation statements)
references
References 89 publications
(83 reference statements)
0
36
0
Order By: Relevance
“…Venditti et al reported that GNPs are used to improve the bioavailability of drugs [ 59 ]. Yet, the practical application of such metal-based nanocarriers can be limited by their potential toxicity [ 60 ]; Polymer-based smart nanocarriers include hydrogels and dendrimers. Dendrimers are large, highly branched polymers capable of loading drugs via entrapment in spaces within the network or by attaching to branching points (via hydrogen bonding or to surface groups via electrostatic interactions) [ 61 , 62 ].…”
Section: Smart Drug Delivery Nanocarriersmentioning
confidence: 99%
See 2 more Smart Citations
“…Venditti et al reported that GNPs are used to improve the bioavailability of drugs [ 59 ]. Yet, the practical application of such metal-based nanocarriers can be limited by their potential toxicity [ 60 ]; Polymer-based smart nanocarriers include hydrogels and dendrimers. Dendrimers are large, highly branched polymers capable of loading drugs via entrapment in spaces within the network or by attaching to branching points (via hydrogen bonding or to surface groups via electrostatic interactions) [ 61 , 62 ].…”
Section: Smart Drug Delivery Nanocarriersmentioning
confidence: 99%
“…Dendrimers and hydrogels have been reported for the efficient delivery of genes, drugs, and proteins [ 66 , 67 , 68 , 69 , 70 , 71 ] and for stimulus-responsive release under various triggers, including temperature, pH, and redox conditions [ 72 , 73 ]. However, dendrimers suffer from their complicated and costly synthesis procedures, and both dendrimers and hydrogels are restricted by their ability to host solely hydrophilic drugs [ 60 ]; Lipid-based nanocarriers include liposomes and micelles. Liposomes, membrane-like self-assembled lipid bilayers, are utilized for the delivery of hydrophobic/hydrophilic drugs, genes, and proteins while possessing high biocompatibility and stimulus responsiveness (e.g., ultrasound and temperature responsiveness) [ 74 ].…”
Section: Smart Drug Delivery Nanocarriersmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, endocytic vesicles have a pH of 5.5–6.0 in endosomes and 4.5–5.0 in lysosomes [ 31 , 32 ]. Therefore, pH-responsive nanocarriers can be designed by using pH differences to control drug release [ 33 ].…”
Section: Endogenous Stimuli-responsive Auncsmentioning
confidence: 99%
“…The large surface area and the ultra-fine size, low toxicity and biocompatibility provide the high potential for the use of nanoparticles in the biomedical field [ 1 , 2 ], in dental restorative materials [ 3 , 4 ], in pharmacology as carriers for targeted drug delivery [ 5 , 6 ] including cancer drugs [ 7 ]. At the same time, many nanoparticles also show antibacterial action.…”
Section: Introductionmentioning
confidence: 99%